A comparison between anorganic bone and collagen-preserving bone xenografts for alveolar ridge preservation: systematic review and future perspectives - Danilo Alessio Di Stefano; Francesco Orlando; Marco Ottobelli; Davide Fiori; Umberto Garagiola (SpringerOpen, 2022)
Abstract After tooth extraction, dimensional changes affect the alveolar socket, leading to loss in alveolar bone height and width. Histological modifications also occur, with initial formation of a blood clot that is replaced with granulation tissue and subsequently with a provisional connective tissue matrix. Spontaneous healing ends with socket filling with woven bone, which is gradually replaced with lamellar bone and bone marrow. Adequate alveolar ridge dimensions and bone quality are required to assure optimal stability and osseointegration following dental implant placement. When a tooth is extracted, alveolar ridge preservation (ARP) procedures are an effective method to prevent collapse of the post-extraction socket. Heterologous bone is widely chosen by clinicians for ARP, and anorganic bone xenografts (ABXs) made bioinert by heat treatment represents the most used biomaterial in clinical applications. Collagen-preserving bone xenografts (CBXs) made of porcine or equine bone are fabricated by less invasive chemical or enzymatic treatments to remove xenogenic antigens, and these are also effective in preserving post-extraction sites. Clinical differences between anorganic bone substitutes and collagen-preserving materials are not well documented in the literature but understanding these differences could clarify how processing protocols influence biomaterial behavior in situ. This systematic review of the literature compares the dimensional changes and histological features of ABXs versus CBXs in ridge preservation procedures to promote awareness of different bone xenograft efficacies in stimulating the healing of post-extraction sockets.